Польська криза 1980–1981 років в інформаційних документах ЦК КПУ та КДБ УРСР - Бажан, О. (Краєзнавство, 2023)
У статті на основі матеріалів вищого партійного керівництва УРСР, звітно-інформаційних документів Комітету державної безпеки УРСР, архівно-слідчих справ на учасників дисидентського руху в Україні, розкривається вплив страйкового руху у Польщі на початку 1980-х років на українське суспільство, висвітлюється реакція на політичну кризу у сусідній країні різних верств населення. Проаналізовано спецповідомлення, доповідні записки радянських органів державної безпеки, які висвітлюють обговорення діяльності незалежної самоврядної професійної спілки «Солідарність» у робітничому середовищі, у студентських колах, у колах творчої інтелігенції, серед громадян Польщі, задіяних на спорудженні промислових об’єктів в Українській РСР. На конкретних прикладах розкрито політику партійних органів УРСР щодо формування громадської думки навколо робітничих протестів у ПНР. Стверджується, що, незважаючи на політичну цензуру, інформація про діяльність незалежної профспілки «Солідарність» різноманітними каналами проникала в Україну. Розглянуто зусилля силових структур по нейтралізації вогнищ вільнодумства, протестних настроїв Україні на тлі страйкового руху у Польщі в 1960-1981 роках. Based on the materials of the top party leadership of the Ukrainian SSR, reporting and information documents of the State Security Committee of the Ukrainian SSR, archival and investigative cases on the participants of the dissident movement in Ukraine, the article reveals the impact of the strike movement in Poland in the early 1980s on Ukrainian society, highlights the reaction of different population strata to the political crisis in a neighboring country. The author analyzed special messages of the Soviet state security bodies, and reports, which highlighted the discussion of the activities of the independent self-governing trade union “Solidarity” in the working environment, in student circles, among the creative intelligentsia and Polish citizens who were involved in the construction of industrial facilities in the Ukrainian SSR. Using concrete examples, the policy of party bodies of the Ukrainian SSR believers, the clergy, and the religious policy of the Soviet authorities in relation to the Greek Catholic Church. It is noted that in the post-war period, the religious policy of the Soviet authorities was aimed at the complete liquidation of Greek Catholic structures, since this church posed a threat to the successful sovietization of Halychyna and Transcarpathia. For this purpose, in 1946, the Lviv Council was held, at which the liquidation of the union was announced. The author shows how various means were used to liquidate Greek Catholic structures, including repression against the clergy and even murder. The Greek Catholic Church was forced to turn to underground religious activities. The article draws attention to the fact that in the period of Khrushchev’s thaw, as a result of the easing of totalitarian pressure in the country, the return from the camps and the exile of many Greek-Catholic priests, the activities of the Greek-Catholic Church revived somewhat. However, Greek Catholics were still forced to lead an underground religious life, since their religious choice was denied by the authorities. Considerable attention is devoted to the analysis of the religious behavior of believers, in particular, the conduct of underground services by Greek Catholics, the performance of religious rites of the life cycle. The underground Greek- Catholic network is also considered.